The Polymorphic Behaviour of Adjectives in Terminography - de Santiago González, Paula; Grcic Simeunovic, Larisa (Meta, 2017)
Adjectives, while analyzed quite thoroughly in the works of terminologists, have not received enough attention in terminographic applications. Their inclusion, for instance in terminological databases, is low in comparison to that of nouns. However, the study of a specialized language such as karstology shows that adjectives have significant value due to their polymorphic behaviour. Our study shows that, depending on their semantic and syntactic relations with other lexical units, adjectives can provide us with essential information for terminology management and specialized knowledge organization. Semantically, adjectives highlight attributes of object concepts within a field allowing translators to discover more specific concepts, or different aspects of already known concepts. Syntactically, adjectives can present various syntagmatic relations with nouns. While some adjectives constrain the meaning of the noun, constructing other specific lexical units, others reveal the usage of terms (either complex or simple) in context. Our study, which is based on an analysis of a monolingual English corpus, has as its purpose to identify the most relevant attributive adjectives and explain their role in a specialized language such as karstology. We will also reflect on the presence of these adjectives in terminological dictionaries and on their contribution to the conceptual structure of a knowledge field.